2013
DOI: 10.1371/journal.pone.0074080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Host Responses to Mycobacterium tuberculosis Antigens in a Multi-Site Study of Subjects with Different TB and HIV Infection States in Sub-Saharan Africa

Abstract: BackgroundTuberculosis (TB) remains a global health threat with 9 million new cases and 1.4 million deaths per year. In order to develop a protective vaccine, we need to define the antigens expressed by Mycobacterium tuberculosis (Mtb), which are relevant to protective immunity in high-endemic areas.MethodsWe analysed responses to 23 Mtb antigens in a total of 1247 subjects with different HIV and TB status across 5 geographically diverse sites in Africa (South Africa, The Gambia, Ethiopia, Malawi and Uganda). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 21 publications
9
56
0
2
Order By: Relevance
“…For comparative purposes we also included ten additional Mtb antigens identified previously (Rv0867, Rv1009, Rv1733, Rv1737, Rv2029, Rv2032, Rv2034, Rv2389, Rv2450, and Rv3353)2324414748495051525354. Diluted whole blood samples were stimulated for six days and the cytokine levels were assessed by a seven-plex assay (data shown only for IFN-γ, IL-17, TNF-α and IP-10 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For comparative purposes we also included ten additional Mtb antigens identified previously (Rv0867, Rv1009, Rv1733, Rv1737, Rv2029, Rv2032, Rv2034, Rv2389, Rv2450, and Rv3353)2324414748495051525354. Diluted whole blood samples were stimulated for six days and the cytokine levels were assessed by a seven-plex assay (data shown only for IFN-γ, IL-17, TNF-α and IP-10 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that CD4 + T cells from persons who have controlled Mtb infection recognize a very diverse range of antigens (14). Antigenic variation among Mtb strains for CD4 + T cells is minimal and an unlikely mechanism of immune evasion (5).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important finding as household contacts are at high risk, particularly within the first year of developing active Mtb (Fox et al, 2013). Collectively these studies indicate that Rpf IGRAs may overcome the limitations of current commercial IGRAs although as the response to Rpf antigens can vary by location (Sutherland et al, 2013), these studies should be replicated in different settings. Furthermore, given the exposure of individuals to Rpf through, for example, BCG vaccination or nontuberculous mycobacterial disease, the diagnostic performance of Rpf IGRAs should be verified in these populations.…”
Section: Immunodiagnosticsmentioning
confidence: 80%